The origins of developmental gene regulation. Issue 2 (24th January 2017) - Arenas‐Mena, César
SUMMARY: The leap from simple unicellularity to complex multicellularity remains one of life's major enigmas. The origins of metazoan developmental gene regulatory mechanisms are sought by analyzing gene regulation in extant eumetazoans, sponges, and unicellular organisms. The main hypothesis of this manuscript is that, developmental enhancers evolved from unicellular inducible promoters that diversified the expression of regulatory genes during metazoan evolution. Promoters and enhancers are functionally similar; both can regulate the transcription of distal promoters and both direct local transcription. Additionally, enhancers have experimentally characterized structural features that reveal their origin from inducible promoters. The distal co‐operative regulation among promoters identified in unicellular opisthokonts possibly represents the precursor of distal regulation of promoters by enhancers. During metazoan evolution, constitutive‐type promoters of regulatory genes would have acquired novel receptivity to distal regulatory inputs from promoters of inducible genes that eventually specialized as enhancers. The novel regulatory interactions would have caused constitutively expressed genes controlling differential gene expression in unicellular organisms to become themselves differentially expressed. The consequence of the novel regulatory interactions was that regulatory pathways of unicellular organisms became interlaced and ultimately evolved into the intricate developmental gene regulatory networks (GRNs) of extant metazoans.